Medicolegal Approach to the Neck Incisions a Case Report - Sayın, İbrahim and Ekizoğlu, Oğuzhan and Kayhan, Fatma Tülin and Yazıcı, Zahide Mine (The Bulletin of Legal Medicine, 2010)
Cut neck injuries are rare situations that need urgent evaluation and intervention. Although a cut throat injury is mainly a mortal situation, the outcome is directly related with the speed of intervention and the properties of the injury. An important point in cut neck injuries is the forensic evaluation of the injury. This evaluation is mandatory for etiology which will be homicidal, suicidal or accidental. This evaluation also needs to perform with a multidisciplinary approach. This case report presented a male subject which has a cut neck injury with suicidal etiology. Besides the case presentation; multidisciplinary approach as well as forensic evaluation is also presented and discussed. Key words: Neck incision, suicide, forensic medicine